2016
DOI: 10.1021/acs.est.6b03049
|View full text |Cite
|
Sign up to set email alerts
|

Transformation and Sorption of Illicit Drug Biomarkers in Sewer Systems: Understanding the Role of Suspended Solids in Raw Wastewater

Abstract: Sewer pipelines, although primarily designed for sewage transport, can also be considered as bioreactors. In-sewer processes may lead to significant variations of chemical loadings from source release points to the treatment plant influent. In this study, we assessed in-sewer utilization of growth substrates (primary metabolic processes) and transformation of illicit drug biomarkers (secondary metabolic processes) by suspended biomass. Sixteen drug biomarkers were targeted, including mephedrone, methadone, coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(102 citation statements)
references
References 60 publications
(151 reference statements)
11
89
2
Order By: Relevance
“…The faster degradation is probably due to the presence of biofilms on the walls of RM and GS. These results are in agreement with previous studies where selected chemicals degraded faster in the presence of sewer biofilms or suspended than in wastewater …”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The faster degradation is probably due to the presence of biofilms on the walls of RM and GS. These results are in agreement with previous studies where selected chemicals degraded faster in the presence of sewer biofilms or suspended than in wastewater …”
Section: Discussionmentioning
confidence: 87%
“…For EtG, biofilm activities in both the RM and GS reduced its stability in very similar ways (Figure b). The results obtained from the CR indicated that suspended microbes could also affect the stability of EtG, but not that of EtS, in the wastewater alone over the studied experimental period, a phenomenon that was reported recently by Ramin et al…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before identifying consumption or discharge, it is important to know the analytical targets of the drugs in wastewater formed after biotransformation in humans or by microbes in the wastewater environment . Microbial processes in sewer models have been identified to cause substantial degradation of human metabolites of drugs of abuse and thus analytical targets of relevance for WBE . Identification of transformation products (TPs) in biological samples can be performed using mass spectrometry (MS) and/or nuclear magnetic resonance (NMR) .…”
Section: Introductionmentioning
confidence: 99%
“…[7] Microbial processes in sewer models have been identified to cause substantial degradation of human metabolites of drugs of abuse and thus analytical targets of relevance for WBE. [7][8][9] Identification of transformation products (TPs) in biological samples can be performed using mass spectrometry (MS) and/or nuclear magnetic resonance (NMR). [10] Liquid chromatography-high resolution-mass spectrometry (LC-HR-MS) allows for identification of low levels of TPs.…”
Section: Introductionmentioning
confidence: 99%